Testing the water: How communities value, use, impact and manage water-related ecosystem services originating in an urban protected area - Brill, Gregg (Department of Environmental and Geographical Science, 2018)
Freshwater ecosystems and their associated landscape features found in developing cities and urban protected areas are essential components of urban social-ecological systems providing city residents with cultural, provisioning and regulating services, all of which hold value. Understanding these values requires overcoming conceptual and methodological challenges so that the multi-dimensional nature, relating to the varying values, benefits, and trade-offs are understood. Understanding values, benefits and trade-offs is essential for ensuring informed and effective management of these services and the landscapes that provide them. This requires the development of tools and methods to predict how changes in land-use and management practices might affect the provision of such services. This study contributes to both the methodological and empirical literature by developing integrated and multidisciplinary approaches to assessing the beneficiaries of freshwater ecosystem services in an urban context and recognising the ecological, social and economic values assigned to ecosystem services over multiple spatial and temporal scales. The aim of this thesis was to assess how beneficiaries, stakeholders and managers within a developing city context, recognise, value and manage the multiple diverse ecosystems services associated with freshwater ecosystems as provided by different landscape features originating in an urban protected area. This aim was achieved by establishing who the beneficiaries of freshwater ecosystem services are, uncovering the spatial and temporal relationships these beneficiaries have with landscape features, determining the nature of ecosystem service values, benefits, impacts and trade-offs as experienced by the different users, as well as analysing the management policies and practices associated with urban ES. Drawing on accumulated as well as existing data sets, newly developed methods and approaches were implemented in this study. This work was primarily undertaken in Table Mountain National Park and in Cape Town, South Africa. A comparative analysis of the perceptions of park managers toward ecosystem service governance and management was undertaken in Table Mountain National Park and in Tijuca National Park, in Rio de Janeiro, Brazil. Natural freshwater ecosystems (e.g. rivers), particularly when combined with built infrastructure (e.g. dams), provide highly valued features in landscapes, delivering multiple cultural services to city residents. Recreation, aesthetic and existence services were valued highest by respondents. People who live closer to the park use, and benefit from, the park's freshwater ecosystems more frequently than those living further away. Park visitors want ease of access in terms of distance to specific freshwater ecosystems, and then once there they want a diversity of activity options, such as recreation opportunities as well as places to reflect and meditate. The outcomes of the cultural-service study in this thesis have important management implications where insights gained can guide management to ensure equitable and sustainable ecosystem service provision to all city residents. To enhance the management of ecosystem services in urban protected areas, it is important to understand the level of inclusion of the ecosystem-service concept in park policy and daily practice. Although management perceptions correspond well with park policy, the concept of ecosystem services is still narrowly developed and needs to be better integrated into the management structures and activities of Table Mountain National Park and Tijuca National Park. Outcomes from this study show that management attention relating to fresh water is still primarily focussed on biodiversity conservation and maintaining system processes and functions. Implementing and enacting the ecosystem services concept largely still needs to happen within parks and urban interfaces. The lack of communication between managers and stakeholders of protected areas makes identifying the beneficiaries of fresh water and valuing ecosystem services difficult, especially when water and associated services flow outside of the park boundaries. An important component of this study was to determine the changes to ecosystem service provision as fresh water flows from a protected area into and across an urban landscape. A scoring system was developed to determine whether changes in land use along three case-study rivers in Cape Town, all of which originate in Table Mountain National Park, positively or negatively impact the provision of water-related ecosystem services. Changes in service provision, over time, were compared to changes in long-term water quality data to verify results from the scoring system. Generally, service levels increased over time along the upper river reaches, whereas the middle and lower reaches of the rivers showed overall declines. The changes to service provision influence the value that urban residents assign to rivers. Findings in this study suggest that the provision of cultural ecosystem services as well as the protection of biological diversity were the key factors considered by those living along the case study rivers as reasons for being willing to pay to protect rivers. Provisioning services were shown to be of less value, as were the economic contribution to property values based on river frontage. This study supports the call for more innovative research to be undertaken in developing countries to break new ground and provide more comprehensive analyses to further our understanding of the values of urban ES. The challenge for environmental researchers in this context is to intensify efforts to understand the relationships between specific landscape elements and freshwater ecosystems and human perceptions, feelings and interpretations, and to express these relationships in ways that are useful for environmental policy and management.